Investors' Behaviour in Punjab - Uppal, Monika (Indian Journal of Finance, 2011)
India's domestic savings as a percentage of its GDP is 28%, which is one of the highest in the world. By 2008-09, the estimates provided by Indicus analyst, a research firm, show that India's total annual personal disposable income has grown to INR 36,059 billion (about 52% being Urban) and the annual savings have grown to INR 9,239 billion, at present. A significant portion of these savings is in the form of investment avenues like gold, fixed deposits, postal schemes and insurance. Net returns from such avenues, on the post-tax basis, could barely outperform inflation. Investment opportunities available in India have been growing in the recent past. The best investment opportunities are often found in the most unlikely places and situations&is affected by changes in government policies, technological innovations, anticipating the future, International trends, and sunrise industries.